Main drivers of the ECB financial accounts and ECB financial strength over the first 11 years - Olivier Vergote; Werner Studener; Ioannis Efthymiadis; Niall Merriman (European Central Bank (ECB), 2010)
This paper analyses the main drivers of the ECB's balance sheet and profit and loss account over the first 11 years of the ECB's existence. Furthermore, the paper assesses the financial strength of the ECB. As monetary policy operations are normally conducted by national central banks under the impulse and instructions from the ECB, the Eurosystem balance sheet is the primary reference for the analysis of Eurosystem monetary policy operations. Three main drivers of the balance sheet and profit and loss account are identified. Firstly, financial market developments and portfolio management decisions imply changes in the value of the foreign reserve and own funds portfolios, which represent a substantial part of the balance sheet (with the share of own funds becoming increasingly larger over the period under review). At the same time, the profit and loss account depends to an important degree on interest income and expenses, realised gains and losses, and write-downs on these portfolios. Secondly, strong banknote demand has gradually increased the size of the balance sheet since the euro changeover in 2002. Banknotes in circulation also provide a strong base for seigniorage income, which is an important item of the profit and loss account. Thirdly, the liquidity-providing operations in foreign currency, which the Eurosystem has undertaken since 2007 in response to the fi nancial crisis, increased significantly the size of the ECB's (and the Eurosystem's) balance sheet. In terms of income and expenses, these operations were rather immaterial at the level of the ECB, although the income generated was substantial at the Eurosystem level. The ECB has remained financially strong over the 11-year period. Factors that support the financial position are strong legislative provisions on e.g. independence and income, the use of financial buffers, seigniorage as a reliable income source and an effective loss-coverage mechanism.
Keywords: D21; D92; E22; E52; 330; central bank balance sheet; central banking; financial accounts; financial strength